The effects of different seating arrangements on Grade 7 students Mathematics performance - Ian V. Paningbatan and Joshel More M. Asis. 4 0 16; 5 (2016)
ABSTRACT: The purpose of this study is to determine the effects of different seating arrangements to then Mathematics Performance of the students and to determine which seating arrangement brings out the highest Mathematics Performance of the students. The researchers will let the students try one seating arrangement each day. After each lesson, the researchers will give a daily quiz to test the students Mathematics Performance that day. The researchers will then analyze the results to find out the effects of each seating arrangement, and to know which one is the most effective for the students. After analyzing the data collected, each seating arrangement gives different effects on the students. The students show good mathematics performance while using their current seating arrangement which in they are randomly assigned by their class adviser. The students show low mathematics performance when they used the very common alphabetical seating arrangement. The students show very good mathematics performance is seated beside a student with high mathematics performance. During the informal interview with the cooperating teacher, he said that can see that the students show more interest with the lesson while using the alternating performance arrangement. With these findings, it can be concluded that the best recommendation is to use the Alternating Performance seating arrangement in Grade 7 students.
Thesis: (Bachelor of Secondary Education with Specialization in Mathematics) - Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2